2017
DOI: 10.1016/j.chemphys.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Resonant photoelectron imaging of deprotonated uracil anion via vibrational levels of a dipole-bound excited state

Abstract: We report both non-resonant and resonant high-resolution photoelectron imaging of cryogenically-cooled deprotonated uracil anions, N1[U-H] ─ , via vibrational levels of a dipole-bound excited state. Photodetachment spectroscopy of N1[U-H] ─ was reported previously [H.T. Liu et al., Angew. Chem. Int. Ed. 53 (2014) 2464], in which forty-six vibrational autodetachment resonances due to the excited dipole-bound state were observed. By tuning the detachment laser to the vibrational levels of the dipole-bound state,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…All the major vibrational peaks and their relative intensities agree with each other in the two spectra, except that the photodetachment spectrum has higher resolution. This resemblance provides strong evidence for the weakly bound nature of the excess electron in the QBS, which has little effect to the neutral core, just as that observed for DBSs [20][21][22][23]. Hence, the photodetachment spectrum of the QBS can be used to yield more accurate vibrational information for the neutral radical.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…All the major vibrational peaks and their relative intensities agree with each other in the two spectra, except that the photodetachment spectrum has higher resolution. This resemblance provides strong evidence for the weakly bound nature of the excess electron in the QBS, which has little effect to the neutral core, just as that observed for DBSs [20][21][22][23]. Hence, the photodetachment spectrum of the QBS can be used to yield more accurate vibrational information for the neutral radical.…”
mentioning
confidence: 71%
“…The latter involves two steps, i.e., resonant excitation to a vibrational level of the QBS, followed by transfer of vibrational energies to the weakly bound electron to induce detachment. The vibrationally induced autodetachment from DBSs generally obeys the Δν ¼ −1 propensity rule under the harmonic-oscillator approximation [45,46] and yields highly non-Franck-Condon PE spectra [20][21][22][23]. This propensity rule is expected to hold true for vibrational autodetachment from the QBS due to the even more weakly bound nature of the QBS electron.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Thea ssignments of all the resonances are based on the calculated vibrational frequencies (Table S2) and the vibrational autodetachment in the resonant photoelectron spectra (Figures 3a-h), which yield tautomer-specific information. We have previously shown that vibrational frequencies in the DBS are the same as those in the neutral states, [33][34][35][42][43][44] that is,t he diffuse dipole-bound electron has little effect on the neutral cores.…”
mentioning
confidence: 95%
“…The data represent an action spectrum for spectral feature B, and hence this behavior indicates coupling between ν 3 and other modes (a breakdown of the normal mode approximation) either in the dipole-bound state itself or as the result of inelastic "rescattering" of the autodetaching electron off the neutral core (the latter explanation has been invoked to explain non-mode specific autodetachment in photoexcitation of uracil and 2-hydroxypyrimidine anions). 44,45 Feature B in the direct detachment spectrum includes contributions from the 6 0 1 , 5 1 1 , 5 0 1 , 9 0 2 , and 6 0 2 bands (Table I). The two step excitationautodetachment sequence v = 0 → ν (v = n) → ν (v = m) produces electrons with kinetic energies equivalent to those of ν 0 m direct detachment channels.…”
Section: Autodetachment-indications Of Mode Non-specificitymentioning
confidence: 99%